Increasing Prevalence of Assisted Living as a Substitute for Private‐Pay Long‐Term Nursing Care - Silver, Benjamin C.; Grabowski, David C.; Gozalo, Pedro L.; Dosa, David; Thomas, Kali S. (Health services research, 2018)
Objective Given the tremendous growth in assisted living (AL) over the past 20 years, it is important to understand how expansion has affected the demand for long‐term care (LTC) provided in nursing homes (NHs). We estimated the effect of a change in county‐level AL beds on the prevalence of private‐pay residents and private‐pay resident days at the NH‐level. Data Sources National census of large AL providers (25+ beds), and Minimum Data Set combined with Medicare enrollment records and claims from 2007 and 2014. Study Design Retrospective longitudinal analysis of LTC markets. Principal Findings Mean AL beds per county increased from 285 to 324, while NHs exhibited a decrease in private‐pay residents (20.1 to 17.7 percent) and resident days (21.3 to 17.5 percent). An increase of 1,000 AL beds at the county level is associated with a reduction of 0.44 percentage points in private‐pay resident days but is not significantly associated with percent of private‐pay residents. Conclusions These results suggest that increases in AL capacity have potentially allowed NH residents to delay or decrease their privately financed lengths of stay. As demand for AL continues to grow, it will be important to assess the effects on other LTC sectors.